UPAYA MENINGKATKAN KEMAMPUAN MEMAHAMI PROSES KEPERAWATAN MELALUI METODE DISKUSI KELOMPOK - Chasanah, Nur (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The nursing process is one approach to solving problems that enable nurses to organize and provide nursing care.The nursing process is very important to understand because it serves as a framework to run functions and responsibilities of nursing in a broad scope.Given the importance of the nursing process that will be used in the treatment of clients either healthy or sick,the nursing students as required understanding of the nursing process.Observations researcher at the second semester freshmen STIKes Dian Husada found understanding of the nursing process is still very low.One of the methods that can be used to enhance the students understanding of the nursing process is the method of small group discussions.The research design used in this research is qulatitatif research. The method used was classroom action research.The population in this study all students at second semester as many as 59 people. Data collected with observations and interviews.Data were analyzed descriptively. Results showed that the method of discussion the students understanding of the nursing process is increasing.Discussion of learning methods can be implementation by educators to improve the achievement of success nursing courses and add to the learning experience of students.Keywords : comprehension, the nursing process, the method of discussion